Islamisasi di Jawa: Kritik atas Islamisation and Its Opponents in Java, Karya Ricklefs - Choirul Fuad Yusuf (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
Islamisation in Java is eventually important in understanding the current dynamic and contemporary affairs in Indonesia, particularly in the aspect of political, cultural, and idio-religous development. Ricklefs in his prominent work, Islamisation and Its opponents in Java, traces up the hitorical root of the Islamic movements in Java which goes back 14 th century. Based on his research of more than 40 years, he highlighted that Islamisation in Java, historically, was the dynamic process of the cultural interaction between Islam and Java. This article of the book review on Islamisation and Its Opponents, endevours to describe analytically of what and how the Islamisation process was methodologically narrated by Ricklefs. In additon, the reviewer intended to analize and evaluate critically the advantage and weakness of the book. Some findings might be underlined that there are still any historical variables need accomplishing as the most comprehensive work of the Islamisation in Java in its era. Keywords: Islamisation, the opponents, indigenous belief and culture, Javanese identity, Islam, Abangan